4b-3(2b-6)=3-(5b+9)

Simple and best practice solution for 4b-3(2b-6)=3-(5b+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b-3(2b-6)=3-(5b+9) equation:


Simplifying
4b + -3(2b + -6) = 3 + -1(5b + 9)

Reorder the terms:
4b + -3(-6 + 2b) = 3 + -1(5b + 9)
4b + (-6 * -3 + 2b * -3) = 3 + -1(5b + 9)
4b + (18 + -6b) = 3 + -1(5b + 9)

Reorder the terms:
18 + 4b + -6b = 3 + -1(5b + 9)

Combine like terms: 4b + -6b = -2b
18 + -2b = 3 + -1(5b + 9)

Reorder the terms:
18 + -2b = 3 + -1(9 + 5b)
18 + -2b = 3 + (9 * -1 + 5b * -1)
18 + -2b = 3 + (-9 + -5b)

Combine like terms: 3 + -9 = -6
18 + -2b = -6 + -5b

Solving
18 + -2b = -6 + -5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '5b' to each side of the equation.
18 + -2b + 5b = -6 + -5b + 5b

Combine like terms: -2b + 5b = 3b
18 + 3b = -6 + -5b + 5b

Combine like terms: -5b + 5b = 0
18 + 3b = -6 + 0
18 + 3b = -6

Add '-18' to each side of the equation.
18 + -18 + 3b = -6 + -18

Combine like terms: 18 + -18 = 0
0 + 3b = -6 + -18
3b = -6 + -18

Combine like terms: -6 + -18 = -24
3b = -24

Divide each side by '3'.
b = -8

Simplifying
b = -8

See similar equations:

| 35+10=35 | | 3p=-48 | | 39+7=28 | | 8a-5-7a=3+5 | | 98=7t | | 18+3x=30 | | -7x+6x+3=0 | | (x-5)/8=-2 | | z+5=14 | | 0=2x^2-20x+50 | | (3X+7)^2=25/49 | | (y-1)/(y+3)+1=(y+4)/(y+6) | | (y-1)/(y+5)=(y-6)/(y+6)+1 | | 68-4x=11-7x | | 3h-1=32 | | -12=-5c-2 | | c=2h+4 | | 65+70=x | | 2x^2=36x-34 | | 25-10(3x-5)=60-15x | | 3x+6=5x+15 | | 32-2-2-2222=1010101 | | (3/x)=(17/x)-5 | | 8x+74=8x+14 | | (2x-3)(3x+2)=18 | | (2/5)=(3/y)-2 | | 3x+2/6*35/23+5x/2=16 | | 1+8/x=5/3 | | (x^2+3)/(x+3) | | x^2-4x-91+y^2-10x+26=15 | | 31.4=2pi;r | | y(y-5)=-4 |

Equations solver categories